Deleuze’s reversal of Platonism: Focus on his criticism of anámnesis - Sonna, Valeria (Aufklärung: journal of philosophy, 2018)
Gilles Deleuze’s critical reception of Plato´s philosophy is developed under the formula of its reversal, the task Nietzsche entrusted future philosophy with. But what does this reversal mean? Deleuze’s reversal of Platonism has been widely discussed. Most of the studies focus mainly on “Platon et le simulacre”, where Deleuze characterizes reversal on the basis of the concept of simulacrum, and his further elaboration in Difference and repetition. An aspect of reversal that has not been considered so far is Deleuze’s reversal of the Platonic image of thought, which is expressed through his critical reading of Plato’s theory of anámnesis. In our paper we show that this criticism is a fundamental core of the task of reversal.